2014
DOI: 10.3906/bot-1307-53
|View full text |Cite
|
Sign up to set email alerts
|

Additions to the Turkish Discomycetes

Abstract: The apothecial ascomycetes that produce cup-shaped ascomata with various colors are commonly known as discomycetes. They represent approximately 9000 taxa, which are saprobic, parasitic, mycorrhizal, or lichenized. Some discomycetes are used in drugs or as biological control agents. Therefore, the fungal resources of the group are significant for biodiversity conservation (Gargas

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 2 publications
1
8
0
2
Order By: Relevance
“…Accord ng to the current l terature Akata and Doğan, 2015;Akata et al, 2013;2014a;2014b;Çolak et al, 2015;Dem rel et al, 2015;Güngör et al, 2015a;2015c;Kaya 2015;Sesl and Denchev, 2008;Solak et al, 2015;Uzun et al, 2014; W th the present study, Las osphaer a ov na s reported for the f rst t me from Turkey at fam ly level and t w ll be the f rst member of th Turk sh 36 larger Ascomycete fam ly.…”
Section: Discussionsupporting
confidence: 61%
“…Accord ng to the current l terature Akata and Doğan, 2015;Akata et al, 2013;2014a;2014b;Çolak et al, 2015;Dem rel et al, 2015;Güngör et al, 2015a;2015c;Kaya 2015;Sesl and Denchev, 2008;Solak et al, 2015;Uzun et al, 2014; W th the present study, Las osphaer a ov na s reported for the f rst t me from Turkey at fam ly level and t w ll be the f rst member of th Turk sh 36 larger Ascomycete fam ly.…”
Section: Discussionsupporting
confidence: 61%
“…In an earlier study we reported 7 new records for the Turkish mycota (Sesli, 2014). The total number of ascomycetous fungi recognized as occurring in Turkey increased to 217 with the recent study by Uzun et al (2014). Lichenized and lichenicolous fungi of Gevne valley (Konya, Antalya) were documented by Kocakaya et al (2014).…”
Section: Introductionmentioning
confidence: 99%
“…Eighty-nine species have previously been reported from the region by local studies (Uzun et al, 2009(Uzun et al, , 2010a(Uzun et al, , 2010b(Uzun et al, , 2013(Uzun et al, , 2014Kaya et al, 2010). Together with the newly determined 112 species, the total current taxa number is increased to 201.…”
Section: Discussionmentioning
confidence: 99%